“KATAPAI” SMOKED FISH AS A TYPICAL DELICACY IN THE COASTAL AREA OF NORTH BUTON REGENCY - Muchtar, Febriana (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2024)
Fish is a high-quality protein animal food source. Unfortunately, fish is perishable that it requires certain preservation and processing methods to prevent spoilage in both fresh fish and processed fishery products. Coastal food resources, particularly seafood, can become culinary specialties that become the icon of their place of origin. This research presents an overview of smoked fish as a typical culinary specialty in the coastal area of North Buton Regency. In this descriptive research, survey was performed to gain data to be narratively presented. The results of this research show that local smoked fish products called "katapai," are a unique culinary delight of North Buton. Katapai is smoked tuna and skipjack sold immediately after the smoking process. People usually enjoy the food with tomato sauce and processed rice called buras. Innovation in smoking techniques, presentation, and packaging are necessary for the development of katapai production in order to extend its shelf life.